A study of fatty acid production by Clostridium butyricum. - Husnul Azan Bin Tajarudin (2012)
This thesis investigates the fatty acid production from carbohydrates using C. butyricum. In nature a common route for the anaerobic degradation of carbohydrate in the environment is via methanogenesis. At the heart of these processes however, is the metabolism of a diversity of carbohydrate materials that produce a few fatty acids (acetate and butyrate) which are then slowly converted to methane. In this context, fatty acids can be considered as a common end- product/intermediate from carbohydrate degradation that could be used to produce chemicals. Already, acetic and butyric acid are important feedstock chemicals in the pharmaceutical, food and industrial sectors and there is potential to expand this further. As a first step to investigate the conversion of waste carbohydrate to fatty acids for chemical production, C. butyricum, a strictly anaerobic bacterium, was investigated as a model system for the potential production of acetic and butyric acid. The production efficiency of C. butyricum relies on the type of substrate, production methodology, the strain and environmental conditions. Pure cultures of C. butyricum were investigated for fatty acid production from carbohydrates. Initial studies involved medium optimization in test tube culture for high growth rate and maximum biomass production (ODmax)- In this medium, glucose was selected as the main substrate together with yeast extract, KH2PO4 and NH4(SO)4. The studies were carried out in three types of pH controlled reactors; batch stirred tank (SRT), continuously stirred tank (CSTR) and membrane bioreactor (MBR) A comparison the fatty acid production kinetics and productivity in each reactor was undertaken and the effect of glucose concentration and where appropriate, glucose feed rates, were also investigated. The results show that fatty acid production could be carried out in all three fermentation systems. A common observation in these systems was that fatty acid production was influenced by the glucose concentration in that at low glucose concentration the ratio of acetate to butyrate was about 30:1 while at higher concentrations the ratio was reduced to about 3:1 on a molar basis. The detailed kinetic studies generated unique data for this organism and shows that the maintenance coefficient (ms) increase with increasing glucose concentration (0.02 to 1.1 g substrate/g cell/h), due to mainly to end product inhibition and the true yield (Yx/s was around 0.2 for all glucose concentrations tested. Meanwhile substrate saturation (KJ decreased with increasing glucose concentrations (2.06-6.41 g/L). This observation was atypical to that observed in other anaerobic fermentations by previous workers. A comparison of fatty acid productivities using a l0g/1 glucose feed in the 3 reactors for acetic acid were 0.95 g/l/h for STR. 4.41 g/l/h for CSTR and 37.88 g/l/h for MBR and for butyric acid 0.15 g/l/h for STR, 1.27 g/l/h for CSTR and 14.34 g/l/h MBR. Although, previous work in this area is limited the data obtained in this study was also compared with other published work and this suggests that the production of fatty acid, especially acetic and butyric acid in the MBR system is by far the most productive yet reported. The results are discussed in the context of the waste treatment process for fatty acid production and its application to waste conversion and its further development.